Penerapan Metode Menghafal dan Problematikanya dalam Pembelajaran Al-Qur’an - Eko Hadi Wardoyo (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
This study aims to describe the application of the method of memorization and its problems in learning Al-Qur'an. This type of research is library research using a qualitative descriptive approach. The data collection technique uses the documentation method. The data analysis technique step in this research is to use content analysis. The results of the research in stage (1) the memorization strategy were the teaching stages, the teaching approach and the use of teaching principles. In stage (2) the technique of applying the memorization method is by understanding the verses to be memorized, repeating before memorizing, listening before memorizing, writing before memorizing. In stage (3) the implementation of Al-Qur'an learning, classical form learning, in private, post test and evaluation.